Novel Quad-band Patch Antenna Design for Wireless Communications in 2.4, 5.2, 5.6 and 5.8 GHz Bands using Genetic Algorithm Optimization - jayasinghe, J.M.J.W.; Uduwawala, D.N. (International Journal of Engineering and Technology, 2012)
This paper presents the design of a novel quad band patch antenna for wireless communications in 2.4, 5.2, 5.6 and 5.8 GHz Bands. Antennas operating in these bands are available in various sizes and used in small hand-held devices as well as in wireless local area networks. A substrate with dielectric constant 3.2 and thickness 3.175mm is used for the design. The patch dimensions (40 × 30 mm) are similar to that of the conventional rectangular patch for the center frequency of the lowest frequency band which is 2.4 GHz. The antenna is fed by a 50? coaxial cable. Genetic algorithm optimization (GAO) is used to optimize the patch geometry and feed position. Simulations are carried out by using HFSS. The optimized antenna resonates at 2.4 GHz with fractional bandwidth of 4.1% and at 5 GHz bands with fractional bandwidth of 33.5%.